2021
DOI: 10.1080/14737167.2021.1927716
|View full text |Cite
|
Sign up to set email alerts
|

Budget impact analysis of medicines: estimated values versus real-world evidence and the implications

Abstract: Objectives: Budget Impact Analyses (BIA) of medicines helps managers in promoting health systems' sustainability when assessing the role and value of new medicines. However, it is not clear whether BIAs typically underestimate or overestimate the impact on real-world budgets. This retroactive analysis seeks to compare estimated values obtained by a BIA and Real-World Evidence (RWE) to guide discussions. Methods: The estimated values were obtained through a BIA concerning the incorporation of adalimumab for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
5
0
1
Order By: Relevance
“…Faleiros et al (Faleiros et al, 2022) compararam os valores de uma AIO da incorporação do adalimumabe para o tratamento de artrite reumatoide com as evidências de mundo real, e os resultados do estudo demonstraram que os custos estimados para cinco anos foram 463,3% maiores do que os custos de mundo real. Esse estudo também considerou que dois fatores foram os principais causadores da divergência: a estimativa incorreta da população e a variação de preços do medicamento ao longo dos anos (Faleiros et al, 2022). A AIO demonstra apenas a estimativa dos gastos para o detentor do orçamento em função da adoção de uma alternativa terapêutica, não sendo de sua abrangência verificar os benefícios para a saúde e para a economia.…”
Section: Discussionunclassified
“…Faleiros et al (Faleiros et al, 2022) compararam os valores de uma AIO da incorporação do adalimumabe para o tratamento de artrite reumatoide com as evidências de mundo real, e os resultados do estudo demonstraram que os custos estimados para cinco anos foram 463,3% maiores do que os custos de mundo real. Esse estudo também considerou que dois fatores foram os principais causadores da divergência: a estimativa incorreta da população e a variação de preços do medicamento ao longo dos anos (Faleiros et al, 2022). A AIO demonstra apenas a estimativa dos gastos para o detentor do orçamento em função da adoção de uma alternativa terapêutica, não sendo de sua abrangência verificar os benefícios para a saúde e para a economia.…”
Section: Discussionunclassified
“…Also, this applies not only to pharmaceutical sales forecasts submitted by market authorisation holders to payers. In a budget impact analysis from Brazil, the estimated costs for adalimumab for the treatment of rheumatoid arthritis were overestimated by 463% (US $ 4.7 billion) due to uncertainties in the number of patients treated and to variations in prices (Faleiros et al, 2021). In a study from Thailand, the theoretically estimated constant budget impact per patient and year for the treatment of lung cancer with pemetrexed was initially overestimated by 34% (US $ 11,881 vs. 8,834) (Sooksriwong and Chanjaruporn, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This requires standardization of methodology, e.g., based on the ISPOR report (Sooksriwong and Chanjaruporn, 2011). We are aware of the fact that this per se cannot solve the problem (Faleiros et al, 2021). However, valid international, cross-system comparisons may be useful to provide answers to the following non-exhaustive list of questions: are prevalence data consistently inaccurate?…”
Section: Discussionmentioning
confidence: 99%
“…Careful cost-effective analysis helps more effectively balance intervention costs with savings through proactive interventions and increased quality of life benefits. In the case of PCSK9 inhibitors, some researchers suggested that overestimates of budget impact by healthcare system decision makers contributed to current reimbursement structures 8,9) . And prelaunch predictions of the budget impact of newly developed drugs were reported to be considerably overestimated versus the actual sales; furthermore, PCSK9 inhibitors had a higher than average prediction "error" 8) .…”
Section: See Article Vol 30: 000-000mentioning
confidence: 99%